Prevalence of coronary macro- and micro-vascular dysfunctions after drug-eluting stent implantation without in-stent restenosis. (1st November 2016) - Hokimoto, Seiji; Tabata, Noriaki; Yamanaga, Kenshi; Sueta, Daisuke; Akasaka, Tomonori; Tsujita, Kenichi; Sakamoto, Kenji; Yamamoto, Eiichiro; Yamamuro, Megumi; Izumiya, Yasuhiro; Kaikita, Koichi; Kojima, Sunao; et al.
Abstract: Background: The aim was to examine the prevalence and characteristics of epicardial vasomotor abnormality (EVA) and coronary microvascular dysfunction (CMD) including endothelium-dependent (EDCMD) or -independent (EICMD) in patients following a second-generation drug-eluting stent (second DES) implantation without in-stent restenosis. Methods and results: In 105 patients who underwent second DES implantation in the left anterior descending coronary artery (74 men; mean age, 67.9±9.6years), and in 105 suspected angina patients without stenting (65 men; mean age 66.4±9.1years), we evaluated EVA using the acetylcholine provocation test, EDCMD and EICMD by measuring the coronary flow reserve and the relationship between myocardial ischemia (intracoronary lactate production between aorta and coronary sinus and ST-T changes) or recurrent angina and vascular function. There was no difference in the incidence of EVA between DES and control (49.5% versus 55.2%; P  = 0.41). Given that the prevalence of CMD was higher in DES than in control (59.0% versus 29.5%; P  < 0.001), CMD may be associated with stent placement. Of the CMD patients, EDCMD alone, EICMD alone, and both CMDs were found in 40.3%, 22.6%, and 37.1%, respectively. Myocardial ischemia was detected in 42.4% of patients, and recurrent angina was more common in the presence of both EDCMD and EICMD in patients with EVA or CMD compared to patients with normal vascular function (EVA, 42.9% versus 7.7%, P  = 0.015: CMD, 39.1% versus 7.7%, P  = 0.007). Conclusions: Myocardial ischemia and recurrent angina may be caused by the presence of both EDCMD and EICMD after a second DES implantation without ISR.